(untitled) (Vietnam Journal of Community Medicine, 2026)
This descriptive case series included three adult men with recurrent complex fistula-in-ano managed in the Department of General Surgery, Transport Hospital. Preoperative pelvic MRI mapped fistula tracts; sphincter-preserving surgery (selective fistulotomy and staged seton for horseshoe tracts) was performed, followed by standardized ERAS-based postoperative care. Early outcomes were favorable with a hospital stay of approximately 7–8 days, no fecal incontinence, and no early recurrence at 1-month follow-up; wounds healed satisfactorily. MRI-guided, sphincter-sparing surgery combined with ERAS appears feasible and effective in the short term; larger cohorts with longer follow-up are warranted.